If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -23 = 2x + 37 Reorder the terms: -23 + 8x = 2x + 37 Reorder the terms: -23 + 8x = 37 + 2x Solving -23 + 8x = 37 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -23 + 8x + -2x = 37 + 2x + -2x Combine like terms: 8x + -2x = 6x -23 + 6x = 37 + 2x + -2x Combine like terms: 2x + -2x = 0 -23 + 6x = 37 + 0 -23 + 6x = 37 Add '23' to each side of the equation. -23 + 23 + 6x = 37 + 23 Combine like terms: -23 + 23 = 0 0 + 6x = 37 + 23 6x = 37 + 23 Combine like terms: 37 + 23 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| (3x+5)(7x^2-2x+1)= | | 5+4x=3x^2 | | -2x^2-12x-18=0 | | 10x^2-50x+40=0 | | (a-4)(6a^2+10a-3)= | | 3x^2=4x+5 | | X^2+2-2lnx=0 | | -5x^2-9x=0 | | 4g-10=4g-4 | | -3+x=-3 | | (p+2)(2p^2-5p+4)= | | X^2-2lnx=-2 | | y=2x^2+20x+51 | | (2m+5)(3m-7)= | | (2h-1)(h-4)= | | 3(2q-5)=36 | | (d+4)(d-3)= | | -t-12=9+7t | | 1(14x-7)=21 | | 2x(x+6)=3x(x-3) | | 7(14x-7)=21 | | 4=4x+8 | | 2y-3=17-8y | | 2x-3=2x | | 5+3p^2=17 | | 1-8z+6-6z=0 | | 2x-7-(x-5)=0 | | -24=6(5-3x) | | n^2-4n-18=3 | | 15c^2=96 | | 13-36x^2=-12 | | 12=5b-2a |